The Influence of the International Maritime Organization (Imo) Annex 375 Policy and Extraordinary Pioneer Services on Operational Efficiency and its Implications on the Voyage Cost of User Ships in the Strait of Malacca and Singapore - Osmond, Agung Pratama; Simanjuntak, Marihot; Susilo, Hary (Dinasti International Journal of Digital Business Management, 2025)
This study addresses the urgency of improving operational efficiency and reducing voyage costs for service-user vessels operating in the strategic Malacca and Singapore Straits. It aims to examine the influence of the International Maritime Organization (IMO) Annex 375 policy and exceptional pilotage services on operational efficiency and their implications for voyage costs. Adopting a descriptive quantitative approach, data were collected through surveys using questionnaires distributed online and offline, supported by documentation. The research population comprised all vessels served in 2024, with a sample of 142 respondents—vessel officers (captains, chief mates, and chief engineers) directly involved in navigation and pilotage services—selected using Slovin's formula. Data analysis employed Structural Equation Modeling (SEM) via SmartPLS. Results reveal that both the IMO Annex 375 policy and exceptional pilotage services significantly enhance operational efficiency, which in turn positively reduces voyage costs. These findings highlight that implementing international maritime policies and optimizing pilotage services can strategically improve port competitiveness and user satisfaction. The study recommends aligning pilotage service SOPs with IMO standards and strengthening pilotage personnel capabilities to meet the challenges of increasingly complex and competitive global shipping